Samson, Antigone, and the charismatic agonistes: From a "pro‐power" to a "pro‐existence" political engagement. (23rd November 2020) - Untea, Ionut
Abstract: In this essay, I argue that the agonistic approach toward political engagement places too much emphasis on the task of winning the social game and overlooks the dimension of what has been called ever since Greek Antiquity by the name charis . Charis is the quality of life, denoting ideals of reciprocal invitations to feel joy and satisfaction. Under the influence of the Weberian model of charismatic leadership, collective charisma has faded away from the attention of political theorists. This essay offers arguments for the integration of the collective charis into agonistic political theory but calls for several revisions of this theory. Counterbalancing the overemphasis on winning involves listening and witnessing in the sense of transforming the miracle of charis into the plain words of the logos and the sounds of the phonê that everybody can perceive.